The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2re00049k
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-promoted continuous flow synthesis of thermoplastic polyurethane–silver nanocomposites and their antimicrobial performance

Abstract: Thermoplastic polyurethane-silver nanocomposites (PU-Ag NCs) have considerable potential in many medical applications due to their superior mechanical and antimicrobial properties. Herein, a microwave-promoted flow system is successfully employed for continuous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…† 3.4 X-ray uorescence analysis X-ray uorescence analysis is a widely accepted effective method for determining the qualitative and quantitative composition of a material by irradiating the sample with high-energy X-photons and observing the outgoing X-ray uorescence. 15 This approach provides for the accurate identication of chemical elements with atomic numbers ranging from 16 (sulphur) to 92 (uranium). The experimental results indicated that the wt% of the doped element were almost coincides with the actual amount doped into the TiO 2 lattice given in Table 3.…”
Section: Morphology Studymentioning
confidence: 99%
See 1 more Smart Citation
“…† 3.4 X-ray uorescence analysis X-ray uorescence analysis is a widely accepted effective method for determining the qualitative and quantitative composition of a material by irradiating the sample with high-energy X-photons and observing the outgoing X-ray uorescence. 15 This approach provides for the accurate identication of chemical elements with atomic numbers ranging from 16 (sulphur) to 92 (uranium). The experimental results indicated that the wt% of the doped element were almost coincides with the actual amount doped into the TiO 2 lattice given in Table 3.…”
Section: Morphology Studymentioning
confidence: 99%
“…12,13 Thus, microwave-assisted synthesis is one of the prospective tools to ameliorate the quality of life in the eld of nanoscience and technology, resulting in a substantial advancement in the large-scale synthesis of numerous functional metal oxide nanomaterials with novel structures and properties. 14,15 Also, because microwave radiation is so important and involved in making metal oxide nanomaterials, it can be used to make doped semiconductor nanomaterials that are active in visible light.…”
Section: Introductionmentioning
confidence: 99%